(untitled) (Herald of the National Children’s Medical Center, 2025)
The evolution of pediatric cardiac surgery highlights the need to improve postoperative management, in particular infusion therapy. The choice of the initial infusion solution remains controversial, with different approaches around the world. Recent data suggest that buffered acetate solutions can stabilize hemodynamics better than 0.9% saline solution in postoperative conditions.